The potential of understorey plants from Gunung Gede Pangrango National Park (West Java, Indonesia) as cervixs anticancer agents - YANIETA ARBIASTUTIE; DJOKO MARSONO; MAE SRI HARTATI; RISHADI PURWANTO (Society for Indonesian Biodiversity, 2017)
Abstract. Arbiastutie Y, Marsono Dj, Hartati MS, Purwanto R. 2017. The potential of understorey plants from Gunung Gede Pangrango National Park (West Java, Indonesia) as cervixs anticancer agents. Biodiversitas 18: 109-115. This study aims to screening 97 species obtained from the understorey plants of The Gunung Gede Pangrango National Park of West Java, Indonesia as the anticancer cervixs agents. The anticancer plant activity is determined by the cytotoxicity assay of understorey plant methanol extracts against HeLa cervixs cancer cells using MTT test method. IC50 which is an indicator of cytotoxicity is determined by the probit analysis. The results show that of the 97 plants tested, there are five potential anticancer plants i.e. Physalis peruvianaL. (Solanaceae), Tithonia diversifolia (Hemsl.) A. Gray (Asteraceae), Lantana camara L. (Verbenaceae), Clidema hirta (L). D.Don (Lamiaceae), and Solanum torvum Sw (Solananceae) with IC50 values of 67.85 µg/mL, 3.38 µg/mL, 43.54 µg/mL, 36.93 µg/mL, and 59.09 µg/mL respectively. The phytochemical compound find five understorey plants consisting of alkaloids, steroids, terpenoids, phenol, flavonoids and tannin. Keywords: Anticancer, Gunung Gede Pangrango National Park, HeLa, MTT assay, understorey plant